Pathological Mechanisms Linking Diabetes Mellitus and Alzheimer’s Disease: the Receptor for Advanced Glycation End Products (RAGE) - Kong, Yanyan; Wang, Fushuai; Wang, Jiao; Liu, Cuiping; Zhou, Yinping; Xu, Zhengqin; Zhang, Chencheng; Sun, Bomin; Guan, Yihui (Frontiers in Aging Neuroscience, 2020)
Diabetes and Alzheimer’s disease (AD) place a significant burden on health care systems in the Western world and its aging populations. These diseases have long been regarded as separate entities; however, advanced glycation end products (AGEs) and the receptors for AGEs (RAGE) may be a link between diabetes and AD. In our study, mice injected with AGEs through stereotaxic surgery showed significant AD-like features: behavior showed decreased memory; immunofluorescence showed increased phosphorylated tau and APP. These results suggest links between diabetes and AD. Patients with diabetes are at a higher risk of developing AD, and the possible underlying molecular components of this association are now beginning to emerge.